Sistem Informasi Penerimaan Peserta Didik Baru UPT SPNF SKB Belitung Menggunakan Metode Rapid Application Development Berbasis Web - Elfaditiya Wardaya; Rusydi Umar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
UPT SPNF SKB Belitung is a non-formal school under the education office located in Belitung Regency. UPT SPNF SKB Belitung has 3 equivalence education packages, namely packages A, B, and C. The system for accepting new prospective students is still being carried out conventionally , namely prospective students must come directly to the UPT SPNF SKB Belitung office to register, As a result, it is less efficient in the use of time, distance, cost and energy. To convey registration information, banners are still being distributed in certain locations, as a result, the delivery is still not comprehensive. The process of inputting registration data for new prospective students is done manually so that problems occur such as difficulty in reading the handwriting of prospective new students, errors in inputting prospective student data and can result in the scattering of important documents for prospective new students. With the construction of this system, it can make it easier for registration staff and new students to carry out the registration process and processing student registration data. The method used to build website for UPT SPNF SKB Belitung is the RAD (Rapid Application Development) method.testing Black box is used to conduct testing on this system, the results of these tests are the system runs without any problems, all the features contained in the system function properly and are in accordance with user needs. With this system, it can make it easier for prospective new students to find information and register without having to come directly to the UPT SPNF SKB Belitung office and make it easier for admins as administrative staff to verify registration data online and process registration report data for prospective new students.